2018
DOI: 10.1111/bjop.12338
|View full text |Cite
|
Sign up to set email alerts
|

Does your mindfulness benefit others? A systematic review and meta‐analysis of the link between mindfulness and prosocial behaviour

Abstract: Mindfulness-based meditation practices have received substantial scientific attention in recent years. Mindfulness has been shown to bring many psychological benefits to the individual, but much less is known about whether these benefits extend to others. This meta-analysis reviewed the link between mindfulness - as both a personality variable and an intervention - and prosocial behaviour. A literature search produced 31 eligible studies (N = 17,241) and 73 effect sizes. Meta-analyses were conducted using mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
235
6
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(295 citation statements)
references
References 94 publications
18
235
6
4
Order By: Relevance
“…Neben dem Gesundheitsbereich wird Achtsamkeit insbesondere im zwischenmenschlichen Kontext weithin als nützlich verstanden. Erst kürzlich erschien eine Meta-Analyse, die über 13 Studien hinweg einen positiven Effekt von Achtsamkeitsinterventionen auf prosoziale Reaktionen zeigt (Donald et al 2019). Die geringe Zahl an eingeflossenen Studien zeigt allerdings, dass dieser Forschungsbereich noch in den Kinderschuhen steckt (Creswell 2017).…”
Section: Prosoziale Und Moralische Reaktionenunclassified
See 1 more Smart Citation
“…Neben dem Gesundheitsbereich wird Achtsamkeit insbesondere im zwischenmenschlichen Kontext weithin als nützlich verstanden. Erst kürzlich erschien eine Meta-Analyse, die über 13 Studien hinweg einen positiven Effekt von Achtsamkeitsinterventionen auf prosoziale Reaktionen zeigt (Donald et al 2019). Die geringe Zahl an eingeflossenen Studien zeigt allerdings, dass dieser Forschungsbereich noch in den Kinderschuhen steckt (Creswell 2017).…”
Section: Prosoziale Und Moralische Reaktionenunclassified
“…Anstatt darüber zu diskutieren, ob es nun einen prosozialen Effekt von Achtsamkeit gibt oder nicht, sollte zunächst die theoretische Ebene im Fokus stehen: Warum sollte erhöhtes prosoziales Verhalten nach einer Achtsamkeitsübung überhaupt auftreten? Donald et al (2019) führen mehrere mögliche Erklärungen an: Davon bezieht sich eine auf generell erhöhte Aufmerksamkeit und eine andere auf erhöhtes Mitgefühl. Beide Erklärungen führen je nach Situation zu verschiedenen Vorhersagen.…”
Section: Prosoziale Und Moralische Reaktionenunclassified
“…suggested that small doses of mindfulness training (half-day training) are sufficient to increase job productivity, but that larger doses (six-week training) are needed to improve attentional focus at work, job satisfaction, and work-life balance. The systematic review by Donald et al [30] found a positive relationship between mindfulness (both operationalised as a personality variable and as an intervention) and prosocial behaviour.…”
Section: Individual-focused Secondary Health Intervention: Mbsrmentioning
confidence: 99%
“…Several researchers and Buddhist scholars, however, have underlined the joint nature of mindfulness and ethics; and mindfulness meditation's potential role in enhancing wholesome behaviors [39,40]. In line with these assertions, investigations into the relationship between mindfulness and ethics have successfully demonstrated mindfulness training dependent improvements in moral reasoning ability [41,42], prosociality [43,44], as well as an association between trait levels of mindfulness and ethical decision making [45]. Improvements in prosociality have also been documented following other contemplative tradition based interventions such as compassion training [46,47].…”
Section: A Neuroscientific Framework For the Investigation Embodied Ementioning
confidence: 99%